Allelopathy of Bidens sulphurea L. aqueous extracts on lettuce development - C.T.A. CRUZ-SILVA; E.G.C. NASU; F.P. PACHECO; L.H.P. NOBREGA (Universidade Estadual Paulista, 2015)
ABSTRACT Allelochemical compounds are present in tissues of different plants` parts and also in other organisms, being released into the environment and thus affecting plants development. There is evidence that secondary metabolites produced by weeds may exhibit several allelopathic effects. This study aimed to evaluate allelopathic activity based on the interaction of aqueous extracts preparations and their concentrations obtained from Bidens sulphurea (Cav.) Sch. Bip. leaves on germination and seedlings development of Lactuca sativa L. cv. Grand rapids (lettuce). The extracts were obtained from fresh leaves and prepared by infusion, decoction, leaching and grinding methods, at concentrations of 0, 7.5, 15, 22.5 and 30%, with four replications with 25 lettuce seeds. Seven days after the percentages of abnormal seedlings and germination, shoot and root length (cm) were evaluated, while germination speed index (GSI) was daily determined and calculated. The experiment was completely randomized in a 4x5 factorial design, with four extract preparation methods and 5 concentrations. It was found out that the B. sulphurea aqueous extracts did not affect the germination and abnormal seedling development percentages in lettuce seeds. The aqueous extracts and their concentrations showed allelopathic effect for GSI, shoot and root length variables, despite their methods of preparation. This effect is not only inhibitory, but in some cases it was also stimulatory.